Sebuah Survey Kondisi Fisik Atlet Bola Voli Jawa Tengah Pasca PON XXI 2024 di Aceh – Sumatra Utara - Nisak, Habibatun (UNIB Press, 2025)
This study aims to determine the physical condition of Central Java bolavoli athletes after the 2024 National Sports Week held in Aceh-North Sumatra. This research is quantitative descriptive research, data obtained from a survey of athletes' physical condition tests organized by the Central Java Indonesian National Sports Committee (KONI) which was held at the Jatidiri Stadium in Semarang on June 12, 2025. The data collection technique in this study is data sampling, where not the entire population is used but based on criteria, namely Central Java volleyball athletes who take part in Long-Term Regional Training. The results of this study indicate that female athletes generally show a more even physical condition and tend to be in the excellent category in almost all aspects tested, such as flexibility, leg power, arm muscle endurance, abdominal muscle endurance, back muscle strength, leg muscle strength, general endurance, agility, and speed. Meanwhile, male athletes showed greater variation in each component of physical condition, with dominance based on the good and excellent categories, but there were also some aspects that were still in the moderate to deficient category. As a result, there are differences in the consistency of physical conditions between male and female athletes that can be taken into consideration in the preparation and planning of more specific and targeted training programs according to the needs of each group.